When Rejection by One Fosters Aggression Against Many: Multiple-Victim Aggression as a Consequence of Social Rejection and Perceived Groupness - Gaertner, Lowell (2008)
Two experiments examined the hypothesis that social rejection and perceived groupness function together to produce multiple-victim incidents of aggression. When a rejecter’s group membership is salient during an act of rejection, the rejectee ostensibly associates the rejecter’s group with rejection and retaliates against the group. Both experiments manipulated whether an aggregate of three persons appeared as separate individuals or members of an entity-like group and whether one of those persons rejected the participant. Consistent with the hypothesis, participants who experienced both rejection and perceived groupness behaved more aggressively against the aggregate (Experiment 1) and evidenced less favorable affective associations toward the aggregate (Experiment 2) than did participants who did not experience both rejection and perceived groupness.